FAIRNESS IN SANCTIONS: EXPLORING CITIZENS' VIEWS ON WELFARE RECIPIENT PENALTIES - Kootstra, A.; Roosma, F (Journal of Current Research and Review (JCRR), 2023)
This paper examines citizens' attitudes towards the adjustment of welfare benefit payments in the context of job search obligations being neglected. The legitimacy of welfare systems depends on the social acceptance of sanctions for welfare recipients, making citizens' perceptions of benefit cuts crucial. Using a quasi-experimental design, the study analyzes how individuals perceive the justness of various triggering events and the duration of sanctions in determining the fair amount of sanctioning. The research investigates the three normative concepts for justice evaluations: equality, contribution, and need, while incorporating elements of deservingness theory such as control, attitude, reciprocity, and identity. Additionally, the study recognizes that sanctions serve functions beyond redistribution, including influencing the behavior of welfare recipients and serving as a form of punishment. Through a literature review and an examination of the German welfare system, the paper develops a theoretical framework and formulates hypotheses. The empirical analysis confirms that citizens consider general justice principles when evaluating the appropriate level of sanctioning. The study employs vignettes presenting fictitious scenarios to measure participants' perceptions of justice and fairness in welfare benefit sanctions. The findings contribute to the broader understanding of the social legitimacy of welfare state institutions and shed light on the factors influencing citizens' views on the adjustment of welfare benefits. By considering a wide range of triggering events and sanction durations, this research provides a nuanced understanding of the assessment of different reasons for sanctioning. The study's results have implications for policy-making and the design of welfare systems that align with societal norms and expectations.